Fear of crime affects quality of life - Md Sakip, Siti Rasidah; Abdullah, Aldrin (2008)
The current crime situation today creates public anxiety and is a constant source of discussion and debate along the corridors of academia, profesional and parties involved in the field. Almost every day we hear news of crime which increases our feelings of fear and highlights our concern regarding the level of public safety. This anxiety also reflects the Statistical Crime Report from the Royal Malaysian Police (PDRM) indicating an increase in criminal cases from the year 2005 to the year 2007. This fear concerns the dip in quality of life that could affect social activities and the national economic well-being. Feelings of fear of crime exceeding actual crime rate gives an illustration of the ebb of social life today and loss of faith in designs for public safety. Fear of crime affects many people and needs to be taken seriously. Although statistically most people have a low chance of becoming a victim of crime, many people nevertheless fear crime. This scenario occurs because almost everyday we come across reports of crime and violence in Malaysia. There have been many reports of crime: snatch thefts, rapes, and other sex-related crimes, assaults and murders, child abuse and ill treatment of foreign maids, hold-ups and petty thefts, kidnappings, fatal road accidents, etc. With this barrage of media reporting, there is an air of anxiety and fear as to what the future will hold for our Malaysian society and subsequently their quality of life. These reports give the impression that our safety in Malaysia is decreased. This follows the depreciation of Public Safety Index in the Malaysian Quality of Life Index (MQLI) 2004. Therefore, fear of crime has become an important issue of public concern which detracts from the quality of life. This paper will discuss the existing causes of fear of crime and trends of crime in Malaysia as important aspects of deterioration in quality of life of Malaysians. Prevention of crime through environmental design will also be discussed in this paper as it has now become a national initiative in overcoming the stated problem in Malaysia.